2004
DOI: 10.1523/jneurosci.5668-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Mesencephalic Dopaminergic Neurons in Culture by Low-Level Stimulation of Voltage-Gated Sodium Channels

Abstract: We used a model system in which dopaminergic (DA) neurons from embryonic rat mesencephalon undergo spontaneous and selective degeneration as they develop in culture. Here, we show that DA cell loss can be prevented efficiently by low concentrations of the Na ϩ channel agonist veratridine. The survival promoting effect of veratridine was reproduced by, but independent of, glial cell line-derived neurotrophic factor. Neuroprotection by veratridine was exquisitely specific to DA neurons, short-lived after withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
146
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(165 citation statements)
references
References 50 publications
18
146
1
Order By: Relevance
“…When comparing TH 1 cell numbers at 0 DIV (i.e., at the time of plating) and at 10 DIV, we found that more than 70% of these neurons had died in the course of maturation of the cultures ( Fig. 2A), which is in good agreement with previous reports (Salthun-Lassalle et al, 2004;Toulorge et al, 2011). This indicates that the increase in TH 1 cell numbers observed in the presence of OXB is most likely due to a reduction of DA cell demise that is spontaneous in this model system.…”
Section: Oxb Exerts Trophic Effects For Da Neurons Insupporting
confidence: 92%
“…When comparing TH 1 cell numbers at 0 DIV (i.e., at the time of plating) and at 10 DIV, we found that more than 70% of these neurons had died in the course of maturation of the cultures ( Fig. 2A), which is in good agreement with previous reports (Salthun-Lassalle et al, 2004;Toulorge et al, 2011). This indicates that the increase in TH 1 cell numbers observed in the presence of OXB is most likely due to a reduction of DA cell demise that is spontaneous in this model system.…”
Section: Oxb Exerts Trophic Effects For Da Neurons Insupporting
confidence: 92%
“…Primary mesencephalic cultures of E14.5 rat and mouse embryos were prepared as reported 43,44 . Mitochondrial activity.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…Immunohistochemical study with anti-tyrosine hydroxylase antibody by Salthun-Lassalle et al (29) showed that cultured dopaminergic neurons of embryonic rats underwent spontaneous apoptotic cell death, with condensed and fragmented chromatin. When the sodium channel agonist veratridine was applied chronically to the cultures, the apoptosis of tyrosine hydroxylase-positive neurons was prevented by approx.…”
Section: Prevention Of Dopaminergic Neuron Apoptosis By Sodium Channementioning
confidence: 99%
“…In addition, sodium channels contribute to neuronal survival (29), remyelination of demyelinated axons (13, 30 -35), epigenetic selection of particular neurotransmitter phenotype out of the multiple repertories of neurotransmitters (36), and auto-modulation of sodium channel expression per se (37).…”
Section: Introductionmentioning
confidence: 99%